Express TV: Competing In a Cluttered World of Media for Consumer Preferences and Viewership Patterns - Saeed ur Rehman; Syed Amir Saeed; Shahnawaz Khan; Ovais Mufti; Asfiya Ahmad; Taimoor Sultan (Institute of Business Management, 2018)
Express News TV Channel found some reports that their TV channel viewership was declining. In Pakistan, however, the viewership data is managed, still the system is not properly managed and has many loopholes. This can be imagined through the information that one of the most populated area of Karachi, Gulshan Iqbal, TV viewing patterns are evaluated through less than ten people meters. Express news therefore decided to conduct a full survey that included the viewership patterns, the most preferred TV shows, and hosts, morning shows, and anchors. The study revealed interesting facts about the standing of Express News programs and TV viewers' preferences of the same.